Identifying Tax Compliance from Changes in Enforcement: Theory and Empirics - Andrew Bibler; Laura Grigolon; Keith F. Teltser; Mark J. Tremblay (Center for Economic Studies and ifo Institute (CESifo), 2024)
Governments increasingly use changes in tax rules to combat evasion. We develop a general approach to point-identify tax compliance along with supply and demand elasticities; identification requires data on prices and quantities before and after changes in tax enforcement and a demand or supply shifter. We illustrate our approach using data on Airbnb collection agreements, where full enforcement is achieved by shifting the tax burden away from hosts to renters via the platform. We find that taxes are paid on roughly zero to 3.5 percent of Airbnb transactions prior to enforcement.
Keywords: H20; H22; H26; L10; 330; tax evasion; compliance; statutory incidence; tax invariance; Airbnb; sharing economy; voluntary collection agreements